About power thresholds, criteria, kinetics and mechanisms of ignition of explosives by laser pulses and pulsed electron beams; Известия вузов. Физика; Т. 49, № 10 - Lisitsyn V. M. Viktor Mikhailovich; Oleshko V. I. Vladimir Ivanovich; Tsipilev V. P. Vladimir Papilovich; Yakovlev A. N. Aleksey Nikolaevich (2006, 2006)
Заглавие с экрана